A brief orientation to counseling : professional identity, history, and standards - Neukrug, Edward (San Diego: Cognella, 2022)
"The third edition of A Brief Orientation to Counseling: Professional Identity, History, and Standards equips readers with the information and skills they need to develop their professional identity and succeed in their journey to becoming a capable and accomplished counselor. The book offers readers a concise and valuable overview of the history of the counseling profession, current trends, the characteristics of an effective counselor, and professional standards and ethics. It features coverage of professional counseling associations, the credentialing process, and the importance of cultural competence and advocacy in modern practice. Readers are encouraged to discover and nurture their professional identity, and are provided with sage advice for applying to graduate school and finding a job. Throughout, renowned author and counselor Edward Neukrug offers guidance and perspective gleaned from his personal experiences and professional career. Additionally, students are provided with meaningful self-reflection opportunities, hands-on experiential activities, and enlightening case studies to enrich their learning experience. The new edition features updated information regarding professional counseling associations, cross-cultural and social justice competence, ethical concerns, cutting-edge issues such as tele-mental health counseling, the 2016 CACREP standards, and more. A full set of ancillaries to assist in teaching is available, including a sample syllabus, exam questions, vignettes, ethical dilemmas, and videos, among other resources. A succinct yet impactful text, A Brief Orientation to Counseling is an essential resource for courses and programs in counseling."--
Preface -- Section I: Professional identity of the counselor -- What is counseling, and who is the counselor? -- Professional associations in counseling and related fields -- Characteristics of the effective counselor -- Section II: History and current trends in the counseling profession -- Predecessors to the counseling profession: from antiquity to early social work, psychology, and psychiatry -- The history of the counseling profession -- Current issues and future trends in the counseling profession -- Section III: Standards in the counseling profession -- Accreditation in counseling and related fields -- Credentialing in counseling and related fields -- Ethics in counseling -- Culturally competent helping: multicultural counseling and social justice work -- Afterword: Applying to graduate school and finding a job -- Glossary -- References -- Index
Includes bibliographical references (pages 237-256) and index
Keywords: Counselors -- Training of; Counselors -- Vocational guidance; Counseling -- Vocational guidance; Counselors -- Professional ethics; Counseling -- Professional ethics; Counseling -- Professional associations; Counselors -- Professional associations; Counselors -- Cultural competence; Counselors -- Accreditation (Education); Counseling -- History